Corporal punishment of Children by parents: Is it discipline or violence and abuse? - CHAN, Wing Cheong (Institutional Knowledge at Singapore Management University, 2018)
Physical punishment is still used as a means of child discipline by Singaporean parents. Is there a difference between such use of violence and abuse of children which is punishable as a criminal offence? What does Singapore and international law say about the use of punitive force on children by parents and other adults who act in loco parentis? This article argues that there is in fact sufficient evidence that Singapore law implicitly prohibits corporal punishment of children by their parents.